KONSEP KELUARGA HARMONIS DALAM ISLAM - Ahmad Sainul (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Islam is the most perfect religion because it regulates all the lines of life including the harmonious family. Nick Stinnet and John Defrein says six steps to build a harmonious family as dictated by Ida Rosyidah and Siti Nafsiah: preserving religious life in the family, spend enough time with family, interaction among fellow family members so as to create rapport, mutual respect, union in the family, patienly facing crisis in the household.